In vitro response of fungi isolated from orchids in BRIS, Setiu Wetland and mangrove in Morib, to different concentrations of lead - Nurul Aliaa Idris,; Zaiti Muhd Zuhir,; Nor Afiqah Mohd Radzuan,; Nurin Sahira Muda,; Rosnadzirah Izzati Rosli, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Interaction of plants with a mycorrhizal partner is known to mediate plant tolerance towards pollution of heavy metal minerals in soil. For orchids, their relationship with orchid mycorrhizal fungi may enable this largest flowering plant family to adapt to various extreme habitats. On the other hand, mangrove plants are also recognized to have this ability as mangroves are a known sink for heavy metal accumulation. Thus, this study aims to isolate and identify mycorrhizal fungi from two habitats; orchids in beach ridges interspersed with swales (BRIS) soil in Setiu Wetland, Terengganu and from mangrove plants in Morib, Selangor; then investigate their tolerance towards lead (Pb) stress. Isolation from BRIS orchids yield two Rhizoctonia species and Penicillium chrysogenum while Penicillium pinophilum, Aspergillus fumigatus and Aspergillus niger where isolated from mangrove plants in Morib. In vitro tolerance to lead tested with concentrations of 100 mg/L, 500 mg/L and 1000 mg/L of Lead (II) nitrate prepared in potato dextrose agar (PDA), showed that all the isolated fungi from mangrove were able to tolerate Pb even at the highest concentration of 1000mg/L but with a slower growth rate. Further studies must be carried out for the discovery of novel species of mycorrhizal fungi that are able to tolerate heavy metal stress to improve plant adaptation for agriculture.